Enhancing Students’ Narrative Writing Skills through Folktale Films - Agustin, Dery Tria; Yana, Pramugara Robby (Tapis: Jurnal Penelitian Ilmiah, 2024)
This research aimed to improve the writing skills of ninth-grade students at a junior high school in Yogyakarta, Indonesia. The study used a Classroom Action Research (CAR) design, incorporating folktale films as a learning tool. Twenty-eight students (Class A) participated, with collaboration from an English teacher. Data were collected through observations, interviews, and tests, employing a triangulation method. The research consisted of two cycles, following the action research phases: plan, action, observation, and reflection. Results showed a significant enhancement in students' writing skills with the use of folktale films. These films increased confidence and participation in English writing, leading to effective narrative text creation. The students actively engaged in lessons, positively impacting their overall writing abilities, as observed and reflected in improved test scores. The paper concludes with practical implications based on the study's findings.